ANALISIS HAMBATAN BELAJAR MATEMATIKA PADA MATERI OPERASI HITUNG CAMPURAN BILANGAN CACAH DI KELAS IV - Nursaadah, Wida; Karlimah, Karlimah; Nuryadin, Asep; Apriani, Ika Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes learning obstacles in mastering mixed arithmetic operations of whole numbers among fourth-grade elementary school students. The research aims to identify the causes of students’ difficulties and propose effective solutions. A qualitative case study approach was employed, involving 27 students and one teacher from a primary school in Tasikmalaya. Data were collected through observations, interviews, document studies, and diagnostic tests. The findings reveal three main learning obstacles: ontogenic, epistemological, and didactic. Ontogenic obstacles stem from students’ cognitive developmental limitations at the concrete operational stage, hindering their understanding of operation sequences. Epistemological obstacles arise from students’ inability to apply concepts flexibly across different contexts, particularly in word problems. Didactic obstacles are linked to conventional teaching methods and limited use of engaging media, leading to low student motivation and conceptual understanding. The diagnostic test results show that 27 students had very low understanding, nine had low, and four had moderate, with no students achieving high or very high levels. These findings highlight the need for contextual, interactive teaching strategies and concrete media to enhance students’ comprehension and engagement. Recommendations include adopting varied teaching approaches and innovative media tailored to students’ cognitive stages to improve learning outcomes.